Effect of B-site substitution on structural, magnetic and optical properties of Ho2Ti2O7 pyrochlore oxide. (March 2020) - Yadav, Pramod K.; Singh, Pinki; Shukla, Manjari; Banik, Soma; Upadhyay, Chandan
Abstract: Ho2 Ti2 O7 is a prominent quantum material, known for its exotic spin ice state, where structural and electronic properties are coupled. We report the systematic examination of the effects of Fe substitution at the non-magnetic Ti site ( x = 0, 0.05, 0.075, 0.1, 0.125 and 0.15) in Ho2 Ti2 O7 on the structural, optical and magnetic properties. It is found that the optical properties of polycrystalline Ho2 Ti2- x Fe x O7- δ ( x = 0, 0.05, 0.075, 0.1, 0.125 and 0.15) can be tuned through partial substitution of the trivalent Fe 3+ ion for the tetravalent Ti 4+ ion. This Fe substitution not only creates charge-compensating oxygen vacancies but also modifies the optical band gap. A systematic structural, X-ray photoelectron spectroscopy, magnetic and optical analysis reveals that above a critical content of x = 0.1, a possible reduction in the oxygen coordination number (octahedral to tetrahedral) occurs, which appears in the form of high spin to low spin crossover for a fraction of the substituted Fe 3+ ions. These results provide a new route to tune the optical band gap and absorption coefficient of Ho2 Ti2 O7 for magneto-optical applications. Highlights: The magnetic and optical properties of Ho2 Ti2- x Fe x O7- δ show a strong dependence on composition. The spin state of substituted Fe 3+ changes from high spin to low spin. The colour coordinate shifts to the dark blue region for x = 0.15 in the CIE colour space chromaticity diagram.